Human hair in contemporary art: conservation issues and solutions - Amélie Pirotte (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art, 2017)
This study explores the use of human hair in contemporary art threw several artworks from the Belgian artist Hélène de Gottal. She employs the traditional techniques used by spindle lace makers, as well as hairspray, to create masks using her face as a model. Human hair is a fragile organic material, which is sensitive to light,temperature and relative humidity.